EFEKTIVITAS PELAYANAN PASIEN TB DENGAN STRATEGI DIRECTLY OBSERVED TREATMENT SHORT-COURSE (DOTS) DI PUSKESMAS SOKO KABUPATEN TUBAN - jurnalmap map; Nourca Anggun Frenanda; Hadi Susanto; Arini Sulistyowati (MAP (Jurnal Manajemen dan Administrasi Publik), 2021)
The purpose of this study was to determine the effectiveness of TB patient services with the DOTS strategy at the Soko Public Health Center in Tuban Regency when viewed from a process approach. This study uses a qualitative method with a descriptive approach through interviews, observation and documentation. Based on the results of the study, it can be concluded that in terms of effectiveness in terms of the process approach there are still a number of indicators that are not appropriate and do not support the effectiveness itself, the spirit of work is still lacking, there is no reward system that stimulates the leadership to work for the creation of working groups that effective, the absence of effort from individuals and organizations in achieving goals, conflicts that occur are always resolved with reference to the interests of the organization. Some indicators that have been supportive, namely in terms of superiors' attention to employees, mutual trust and communication between leaders and employees have been said to be good, there has been decentralization in decision making as well as vertical and horizontal communication. Because there are still some indicators that do not yet support the service is not yet effective.